Perancangan Sistem Informasi Pendaftaran Rawat Jalan Menggunakan TOGAF ADM dan Kombinasi COBIT 5 - Martianda, Herza; Saepudin, Sudin (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2021)
Bhayangkara Setukpa Hospital Lemdiklat Polri is one of several hospitals located in Sukabumi. Hospitals provide health services, one of which is outpatient registration services. In his service performance Rs. Bhayangkara Setukpa Lemdiklat Polri is still not optimal, in 2017 to 2019 there was an increase in the number of outpatient visits by 50% and in 2020 the decline reached 27%. The current outpatient registration information system is still offline and has a long registration service time because the patient must fill out a form first, while the registration officer is only guarded by two people without being supported by the speed of the registration information system that can be accessed by the patient. Hospitals do not yet have an alternativeregistration online, while in this digital era, hospital services need to be improved by implementing Enterprise Architecture (EA) using TOGAF ADM (The Open Group Architecture Framework Architecture Development Method) and the Combination of COBIT 5 (Control Objective for Information and Related Technology). TOGAF ADM can define the stages of information architecture design and need COBIT 5 support to carry out the stages. EA is useful for fulfilling future business processes. EA design is the right solution in supporting the organization of a business. Therefore, the authors design to support anregistration information system online that is integrated in the process of running the right business at the Hospital. The result of the TOGAF ADM framework and the COBIT 5 Combination is a blue print for EA design in the form of recommendations for IT HR Recruitment, Outpatient Registration Information System Design, Employee Training, and Outpatient Registration Marketing Innovations.